English Teachers’ Perception on Strategies in Teaching Reading Comprehension to Motivate the Students - Nugroho, Toto; Bharati, Dwi Anggani Linggar; Hartono, Rudi (English Education Journal, 2019)
A teacher should have good perception of teaching and strategies to deal with some difficulties that can be aroused in the process of reading. However, the teachers’ background of State Senior High School of Pemalang Regency are various. This condition make different perception when they performed in their teaching English in their classroom. The present study sought to explore English teachers’ perception of learning second language. Motivation is one of the important factors which impacts greatly on language learning. One of the most important factors which receives the special focus in foreign language teaching is reading motivation. More recently, studies on reading motivation have also gained much interest. This review paper is going to consider the impact of reading motivation on reading comprehension. In this paper, the researcher explains the terms of strategies, motivation, reading comprehension, and different models of reading comprehension. The review of this study showed that teachers’ strategies on teaching reading comprehension had a considerably positive effect on reading comprehension activities.